Sera From Children After Cardiopulmonary Bypass Reduces Permeability of Capillary Endothelial Cell Barriers. Issue 7 (July 2018) - Pierce, Richard W.; Zahr, Riad Abou; Kandil, Sarah; Faustino, E. Vincent S.; Pober, Jordan S.
Abstract : Objectives: Children undergoing cardiopulmonary bypass develop clinically impactful capillary leak of unclear etiology. A widely held hypothesis that exposure of circulating cells to the cardiopulmonary bypass circuit induces the release of inflammatory mediators that act to disrupt intercellular junctions of capillary endothelial cells inducing paracellular capillary leak either directly or through new gene expression. Design: Cohort study. Setting: Tertiary pediatric hospital. Patients: Twenty children undergoing surgery with cardiopulmonary bypass for congenital heart disease. Serum was collected before cardiopulmonary bypass, 2 hours after cardiopulmonary bypass, and 18 hours after cardiopulmonary bypass. Interventions: None. Measurements and Main Results: We analyzed the effects of 10% patient sera on the "function, structure, and gene expression" of cultured human dermal and pulmonary microvascular endothelial cells. Changes in barrier "function" were measured using transendothelial electrical resistance. Associations between changes in transendothelial electrical resistance and subject characteristics were analyzed using linear mixed effects model with area under the resistance curve as outcome. Changes in junctional "structure" were assessed by analyzing the organization of the endothelial cell junctional proteins claudin-5 and VE-cadherin using immunofluorescence microscopy. Changes in inflammatory "gene expression" were measured using real-time quantitative reverse transcription-polymerase chain reaction. All serum samples induced a transient, 120-minute increase in transendothelial electrical resistance followed by persistent loss of barrier function. Unexpectedly, sera collected postcardiopulmonary bypass–induced significantly less loss of barrier function in both dermal and pulmonary capillary endothelial cell compared with precardiopulmonary bypass sera. Consistent with the transendothelial electrical resistance results, claudin-5 and vascular endothelial-cadherin junctional staining showed less disruption in cultures treated with postcardiopulmonary bypass sera. Expression of genes commonly associated with inflammation was largely unaffected by patient sera. Conclusions: Contrary to the hypothesis, sera taken from children after cardiopulmonary bypass induces less capillary barrier disruption relative to sera taken from children before cardiopulmonary bypass, and none of the sera induced significant changes in expression of inflammatory genes. Abstract : Supplemental Digital Content is available in the text.